Implementation of Individualized Curriculum for Children with Special Needs in Inclusive Elementary Schools: A Systematic Literature Review in the Context of Palangka Raya - Juhairiah, Siti; Kinasih, Qanaiya Yosheila; Yuwono, Doddy Teguh; Selawaty, Desy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Individualized Curriculum or Individualized Education Program (IEP) is a learning approach designed to accommodate the unique needs of Children with Special Needs (CSN) within inclusive education systems. This study analyzed 24 peer-reviewed articles using the Systematic Literature Review (SLR) method with VOSviewer visualization to identify factors influencing IEP implementation in inclusive elementary schools, particularly within the Palangka Raya context. The review covered literature published between 2015 and 2024 and focused on the planning, execution, and evaluation of IEPs. Findings suggest that IEP success depends significantly on teacher competencies, supportive school policies, parental involvement, and access to adequate resources. While certain schools in Palangka Raya have initiated IEP practices, challenges remain in terms of structural, technical, and cultural barriers. VOSviewer-based visualizations highlight key focus areas in the literature such as